2017
DOI: 10.1111/his.13187
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 expression in triple‐negative breast cancers

Abstract: Our study has demonstrated that GATA3 expression is common in primary triple-negative breast carcinomas. It also suggests that although GATA3 is an oestrogen receptor (ER) regulated gene, it still proves useful in differentiating between primary and metastatic tumours in patients with a history of breast cancer regardless of its molecular subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
3
17
2
Order By: Relevance
“…1,4,6,12,13 Some studies reported GATA3 expression in >90% of HR-positive cancers, whereas only 20-66% of TNBCs showed expression when a certain clone of GATA3 (L50-823) was used. 6,10,[14][15][16][17] The expression rates of GCDFP15 and MGB in TNBCs were even lower (3-31% and 17-26%, respectively), with many positive cases showing only focal staining. 1,4,6,10,16,18 For these reasons, new markers that are more specific and sensitive for TNBC are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,6,12,13 Some studies reported GATA3 expression in >90% of HR-positive cancers, whereas only 20-66% of TNBCs showed expression when a certain clone of GATA3 (L50-823) was used. 6,10,[14][15][16][17] The expression rates of GCDFP15 and MGB in TNBCs were even lower (3-31% and 17-26%, respectively), with many positive cases showing only focal staining. 1,4,6,10,16,18 For these reasons, new markers that are more specific and sensitive for TNBC are needed.…”
Section: Introductionmentioning
confidence: 99%
“…These markers showed high expression in hormonal receptor (HR)‐positive and human epidermal growth factor receptor 2 (HER2)‐positive cancers, but low expression in triple‐negative breast cancers (TNBCs) 1,4,6,12,13 . Some studies reported GATA3 expression in >90% of HR‐positive cancers, whereas only 20–66% of TNBCs showed expression when a certain clone of GATA3 (L50‐823) was used 6,10,14–17 . The expression rates of GCDFP15 and MGB in TNBCs were even lower (3–31% and 17–26%, respectively), with many positive cases showing only focal staining 1,4,6,10,16,18 .…”
Section: Introductionmentioning
confidence: 99%
“…GATA3 has been shown to be associated with the luminal subtype of breast cancer, whereas 88% of estrogen receptor (ER)-negative tumors retained GATA3 expression [15]. Its expression rate in triple-negative cancer ranged from 20.16 to 48% [16, 17] in contrast to 74.6% in apocrine type triple-negative breast cancer [18]. The majority of published studies suggest that loss of GATA3 expression is associated with worse prognosis [19]; however, this is not universally accepted [3].…”
Section: Introductionmentioning
confidence: 99%
“…GATA3, which is a specific transcription factor of the Th2 cytokine [ 31 ], belongs to the zinc finger structure transcription factor GATA family. GATA1-6 is one of the members that interacts with the common sequence (A/T) GATA (A/G) through higher affinity, and has a DNA-binding motif (zinc finger) [ 32 ]. Studies on GATA3 indicated that GATA3 is critical for the growth and differentiation of T cells.…”
Section: Discussionmentioning
confidence: 99%